Quaternary marine mollusks in Tierra del Fuego: insights from integrated taphonomic and paleoecologic analysis of shell assemblages in raised beaches - Gordillo, Sandra (2009)
During the Quaternary the southern tip of South America was affected by several glaciations which might have excluded much of the benthic marine fauna inhabiting this region, with the consequent in-terruption of the connection between the Atlantic and the Pacific Oceans. In that context, fossil marine mollusks recovered from interglacial (Pleistocene) and postglacial (Holocene) Quaternary deposits of Tierra del Fuego, provide a key for the reconstruction of paleocommunities and the evaluation of changes in faunal composition over time. Paleontological database was compiled from previous works, showing a diverse fauna, which includes 91 different species (61.5% gastropods; 31.9% bivalves and 6.6% chitons). Quaternary time-averaged mollusk assemblages from Tierra del Fuego give a very good picture of the overall coastal benthic biodiversity patterns in the region. The composition of mollusk species showed remarkable similarities with present- day fauna, which reinforces the hypothesis that climatic conditions have maintained without significant changes since at least the Middle Pleistocene. However, taphonomic and paleoecological analysis of shell assemblages shows the existence of different shallow benthic com-munities, which represent spatial and temporal variations among regions and sites.